THE IMPACT OF FISCAL CONSOLIDATION AND ECONOMIC GROWTH ON DEBT: EVIDENCE FROM INDIA - Chotia, Varun (Economic Annals, 2019)
This paper analyses the chal-lenges debt reduction faces as a result of fis-cal consolidation and the effect of growth on India’s debt ratio. Simulations are con-ducted based on India’s current revenue and debt levels and project different cases of fiscal tightening and their effect on changes in debt stock with respect to the change in GDP, i.e., changes in the debt ratio. The es-timates for multipliers that are used in the Structural Vector Auto Regression (SVAR) model are obtained empirically by giving shocks to fiscal instruments such as expen-diture and taxes. A non-technical approach to the SVAR methodology is used to anal-yse the dynamics of the studied framework by subjecting it to unexpected shocks. A more measured act of consolidation may be implemented in an attempt to normalise multiplier values in order to create an ap-propriate environment for reducing gov-ernment spending. The drawbacks include the limitations of the SVAR methodology such as the orthogonality condition, which makes the entire analysis fairly restrictive. The framework used for the analysis is a modern approach towards understanding macroeconomic trends and variables in the context of the Indian economy and seeks to apply recently developed analytical tools.